Opinion 2428: Mantis limbata Brullé, 1838 (currently Ameles limbata) (Mantodea, Mantidae, Amelinae): specific name conserved - ICZN (Bulletin of Zoological Nomenclature, 2018)
The International Commission on Zoological Nomenclature has used its plenary power to conserve the specific name Mantis limbata Brullé, 1838 (currently Ameles limbata) by giving it precedence over its senior primary homonym Mantis limbata Hahn, 1835.
Keywords: Nomenclature; taxonomy; Insecta; Mantodea; Mantidae; Amelinae; Stagmomantinae; Ameles; Mantis; Stagmomantis; Ameles canaria; Ameles limbata; Mantis limbata; Stagmomantis limbata; Canary Islands; Central America; North America